The macroeconomics of irreversibility - Isaac Baley; Andrés Blanco (Federal Reserve Bank of Atlanta, 2024)
We study aggregate capital dynamics in an investment model with idiosyncratic productivity shocks, fixed capital adjustment costs, and irreversibility driven by a wedge between capital purchase and resale prices. We derive sufficient statistics capturing the role of investment frictions on aggregate capital fluctuations, measure these statistics with investment microdata, and exploit them to discipline the capital price wedge. Irreversibility doubles the persistence of capital fluctuations and is crucial for reconciling micro-level investment behavior with macroeconomic propagation.
Keywords: D30; D80; E20; E30; 330; investment frictions; capital price wedge; irreversibility; lumpiness; fixed adjustment costs; capital misallocation; Tobin's q; transitional dynamics; inaction; propagation